Perancangan E-Book Ilustrasi Karakter Tokoh Wayang Beber Remeng Mangunjaya - Maharsi, Indiria (Institut Seni Indonesia Yogyakarta, 2024)
ABSTRACTWayang Beber of Wonosari staging the Remeng Mangunwijaya story is a really rare heritage from the ancestors of Indonesian people. At this moment, there are only three wayang beber left that can be found at three places, namely Wonosari and Pacitan, both in Indonesia and the other one is in Leiden, Netherlands. Instead of its priceless importance and existence, there is only very little number of Indonesian people know the ins and outs about this wayang, such as the illustrated sheet as wayang beber’s tangible object and also the performed story. The characters in the story that actually were drawn in unique interesting visuals are not popular too among people. This condition entails the need of a medium to introduce and inform Wayang Beber Wonosari to the audiences. This research aimed at designing an illustrated e-book about the characters in Wayang Beber Wonosari ‘Remeng Mangunwijaya’ and their roles in the story. The design thinking method was employed in the design process covering these five stages: empathizing, defining, ideating, prototyping, and testing. The method was used to identify the users’ needs, define the design problems, and finding the best solutions for those problems. Each stage consisted of several steps to create the most appropriate e-book for the targeted audiences. The designed book presented knowledge about the characters in the story in the form of illustration. This e-book design was one of the methods used to preserve wayang beber known as informational preservation method that would be disseminated online so that the audiences could access it easily. It was also an effort to introduce Wayang Beber of Wonosari to wider target audiences Keywords: Wayang Beber, Remeng Mangunwijaya, Preservation, Illustration, E-book@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;div.WordSection1 page:WordSection1;